Hubungan Usia dan Paritas Dengan Gejala Depresi Postpartum Pada Ibu Nifas - Nur Rohmah; Dearisa Surya Yudhantara; Krisjentha Iffah Agustasari (Universitas Islam Jember, 2025)
Postpartum depression (PPD) is a mood disorder occurring after childbirth, characterized by emotional dysregulation such as persistent sadness, anxiety, and fatigue that interfere with a mother’s ability to care for herself and her infant. In severe cases, PPD may develop into psychotic symptoms, including hallucinations and an increased risk of self-harm or harm to the baby. In Indonesia, the highest prevalence of postpartum depression is reported on Java Island (22%), followed by Sulawesi (20%), Sumatra (18%), Bali (17%), and Kalimantan (15%), with East Java showing the highest provincial rate (20%). This study aimed to analyze the relationship between maternal age and parity with postpartum depression symptoms. A quantitative cross-sectional analytical design was used with 40 postpartum mothers selected through purposive sampling. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) and analyzed using Pearson’s correlation test. The results showed no significant relationship between maternal age and PPD symptoms (p = 0.631) or between parity and PPD symptoms (p = 0.859). Mothers aged 21–35 years showed a higher proportion of moderate to severe symptoms. Overall, maternal age and parity were not significantly associated with postpartum depression symptom (p > 0.05)